2019
DOI: 10.1097/j.pain.0000000000001683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of open-label placebo on pain, functional disability, and spine mobility in patients with chronic back pain: a randomized controlled trial

Abstract: Chronic back pain (CBP) is a major global health problem, while its treatment is hampered by a lack of efficacy and restricted safety profile of common frontline therapies. The present trial aims to determine whether a 3-week open-label placebo treatment reduces pain intensity and subjective and objective functional disability in patients with CBP. This randomized controlled trial, following a pretest–posttest design, enrolled 127 patients with CBP (pain duration >12 weeks) from the Back Pain Center, Neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 35 publications
9
108
0
2
Order By: Relevance
“…After discontinuing or tapering placebo pills, most patients remained improved. Sustained OLP effects were also found in the first two studies including exploratory follow-up phases with cancer patients with chronic fatigue after undergoing chemotherapy 8 and chronic back pain patients 5 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…After discontinuing or tapering placebo pills, most patients remained improved. Sustained OLP effects were also found in the first two studies including exploratory follow-up phases with cancer patients with chronic fatigue after undergoing chemotherapy 8 and chronic back pain patients 5 .…”
Section: Discussionmentioning
confidence: 73%
“…Prescribing placebos in an honest manner would eliminate the ethically problematic use of deceptive placebos or active medications that have no efficacy for the treated condition (“impure placebos”) in the clinical setting 2 . The first randomized controlled trial (RCT) on open-label placebos (OLP) was conducted in 2010 among patients with irritable bowel syndrome 3 , followed by further RCTs on chronic back pain 4 , 5 , depression 6 , allergic rhitinis 7 , and cancer-related fatigue 8 . A meta-analysis from 2017 found an overall positive effect of 0.9, indicating a large effect of OLP compared to no-treatment 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 7 Open-label placebo involves the presentation of the placebo to the patient and explaining the purpose and possible benefits of this option. Moreover, OLP has already been successfully demonstrated in a pilot randomized controlled trial (RCT) in patients suffering from pain 6 , 9 , 10 , 13 and nonpain conditions. 1 , 11 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…There are even open-label placebo trials in the field of back pain, in which patients are told that they would receive placebo, which show positive effects on pain and disability [47,48]. On the other hand, we know that placebo-effects in trials may be exceeding 30% of the total observed effect, and that these placebo effects may not be reflected in clinical practice [49].…”
Section: Expert Opinionmentioning
confidence: 99%